Electrical energy input efficiency limitations in CO2-to-CO electrolysis and attempts for improvement - Reichbauer, Thomas; Schmid, Bernhard; Vetter, Kim Marie; Reinisch, David; Martić, Nemanja; Reller, Christian; Grasruck, Alexander; Dorta, Romano; Schmid, Günter (Electrochemical Science Advances, 2023)
Electrochemical CO2 reduction is a potentially up-coming technology to convert anthropogenic emitted CO2 into chemical feedstock. Due to alkaline operating conditions of CO2-electrolyis in gas diffusion electrodes, exothermal hydroxide ion neutralization with the excess of supplied CO2 leads to unavoidable electricity-to-heat conversion at the cathode, therefore limiting electrical energy input efficiency. The decomposition reaction of carbonates by protons from water oxidation completes the inherent CO2 transport at the anode. In this work, different production routes to CO are thermodynamically examined and experimentally validated. Using formic acid as an intermediate towards CO the electrical energy input efficiency can rise to 71% on a thermodynamical basis. Additionally, the possibility of altering the mechanism of CO2 reduction under acidic conditions is investigated, which would lead to even larger electrical energy input efficiencies. The concept was investigated by pH series measurements (pH = 0–6) at 50 mA/cm2 where Pb derived from Pb3O4 was used as a CO2 reduction catalyst. The reduction to formic acid under acidic bulk electrolyte pH is stable at FEHCOOH = 70% down to pH ≈ 1, while HER is becoming dominant below. Even under such acidic bulk electrolyte conditions no change in reduction mechanism could be forced, which is reflected in invariant cell voltages in the model experiment.
CRIS-Team Scopus Importer:2024-12-16
Keywords: carbon dioxide electroreduction; energy efficiency; formate/formic acid; gas diffusion electrodes; Pb catalyst